Histopathological study of nickel induced alterations in the fresh water bivalve, Lammellidens marginalis - P. Zambare1, A. V. Andhale1*, P. A. Bhosale2 and S. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Chronic exposure for 30 days to nickel chloride (0.227ppm, equivalent to the LC50/10 of 96 hours exposure) showed the results of histomorphological impact on gills and digestive glands of the bivalve, Lammellidens marginnalis. The study revealed that the gill lamellae and hepatic lobule were badly affected by salt of nickel chloride and the severity of the effect was time dependent.